A Fenton-like method using ZnO doped MIL-88A for degradation of methylene blue dyes. Issue 66 (3rd November 2020) - Ren, Gangli; Zhao, Ke; Zhao, Lang
Abstract : MIL-88A with different sizes were prepared by changing the content of ZnO. The prepared nanocomposites were used as catalysts in Fenton-like reaction of removing MB. The effects of the main reaction parameters on the reaction activity were studied. Abstract : MIL-88A with different sizes was prepared by hydrothermal method by changing the content of ZnO. The samples were characterized by SEM, TEM, XRD, XPS and FT-IR. The synthesized material was used for the removal of methylene blue dye in a Fenton-like reaction, and the optimal reaction conditions were studied through single factor experiments. The experimental results show that when the molar ratio of the amount of ZnO introduced to FeCl3 ·6H2 O is 1 : 1, the obtained materials have better catalytic performance than others. Under the optimal conditions, MIL-88A(Fe1 Zn1 ) has the best catalytic performance for 300 mg L −1 methylene blue. The removal rate can reach 96.15% within 40 minutes.